Ultrasound guided percutaneous thrombin injection for the treatment of iatrogenic pseudoaneurysms. Issue 4 (1st October 1999) - Elford, J; Burrell, C; Roobottom, C
Abstract : Iatrogenic aneurysms are usually postcatheterisation pseudoaneurysms of the femoral artery. Until recently, the treatment of choice was ultrasound guided compression repair. A case of pseudoaneurysm of the axillary artery, arising as a complication of pacemaker insertion in an 83 year old man is reported. Compression repair was not possible in this case, and so the aneurysm was occluded by percutaneous ultrasound guided thrombin injection directly into the aneurysm sac. Percutaneous ultrasound guided thrombin injection is a promising new minimally invasive technique for the treatment of iatrogenic pseudoaneurysms.